Analisis Pengembangan Usaha Mikro Kecil dan Menengah dalam Meningkatkan Kesejahteraan Masyarakat di Kecamatan Pujut - Wardiningsih, Reny (Lembaga Yasin AlSys, 2022)
This study aims to determine the development and role of Micro, Small and Medium Enterprises (MSMEs) in improving the welfare of the community in Pujut District, Central Lombok Regency, NTB. This type of research is descriptive qualitative research. The population in this study were all MSMEs in Pujut District. The sampling technique used was random sampling. Data collection techniques using interviews and direct surveys and using secondary data such as literature, books, websites and others. The results of this study indicate that the development of MSMEs in Pujut sub-district has increased, especially after the establishment of the Mandalika circuit has had a tremendous impact and influence on the economic growth of Small and Medium Mikto Business actors. The role of MSMEs in Pujut sub-district can increase family economic income so that it can meet family needs, reduce unemployment and be able to give birth to new business actors. This indicates that MSMEs can improve the welfare of the community in Pujut sub-district.